VOLUNTARY ACTIVITIES AND DAILY HAPPINESS IN THE UNITED STATES. - Gimenez‐Nadal, J. Ignacio; Molina, Jose Alberto (Economic Inquiry, 2015)
This article analyzes differences in daily happiness between those individuals in the United States who perform voluntary activities during the day and those who do not. Using the Well-Being Module of the American Time Use Survey 2010, we find that those who devote any time to voluntary activities during the day report higher levels of daily happiness than those who do not. Comparing the happiness obtained from a range of activities, we find that volunteering is among the most enjoyable, indicating that time spent on voluntary activities is utility-enhancing. We document that the effect of voluntary activities on the experienced utility of individuals can be decomposed into a 'time-composition' effect and an 'activity' effect, with the latter explaining between 11% and 46% of the observed difference. ( JEL D13, J16, J22)